Aurantio-Obtusin Attenuates Non-Alcoholic Fatty Liver Disease Through AMPK-Mediated Autophagy and Fatty Acid Oxidation Pathways - Zhou, Fei; Ding, Mingning; Gu, Yiqing; Fan, Guifang; Liu, Chuanyang; Li, Yijie; Sun, Rong; Wu, Jianzhi; Li, Jianchao; Xue, Xiaoyong; Li, Hongjuan; Li, Xiaojiaoyang (Frontiers in Pharmacology, 2022)
Nonalcoholic fatty liver disease (NAFLD), manifested as the aberrant accumulation of lipids in hepatocytes and inflammation, has become an important cause of advanced liver diseases and hepatic malignancies worldwide. However, no effective therapy has been approved yet. Aurantio-obtusin (AO) is a main bioactive compound isolated from Cassia semen that has been identified with multiple pharmacological activities, including improving adiposity and insulin resistance. However, the ameliorating effects of AO on diet-induced NAFLD and underlying mechanisms remained poorly elucidated. Our results demonstrated that AO significantly alleviated high-fat diet and glucose-fructose water (HFSW)-induced hepatic steatosis in mice and oleic acid and palmitic acid (OAPA)-induced lipid accumulation in hepatocytes. Remarkably, AO was found to distinctly promote autophagy flux and influence the degradation of lipid droplets by inducing AMPK phosphorylation. Additionally, the induction of AMPK triggered TFEB activation and promoted fatty acid oxidation (FAO) by activating PPARα and ACOX1 and decreasing the expression of genes involved in lipid biosynthesis. Meanwhile, the lipid-lowing effect of AO was significantly prevented by the pretreatment with inhibitors of autophagy, PPARα or ACOX1, respectively. Collectively, our study suggests that AO ameliorates hepatic steatosis via AMPK/autophagy- and AMPK/TFEB-mediated suppression of lipid accumulation, which opens new opportunities for pharmacological treatment of NAFLD and associated complications.